Adolescent-to-parent violence in adoptive families - Selwyn, J; Meakings, S (Oxford University Press, 2015)
Adolescent-to-parent violence (APV) has received little attention in the social work literature, although it is known to be a factor in families whose children are at risk of entry to care. The behaviour patterns that characterise APV include coercive control, domination and intimidation. Crucially, parental behaviours are compromised by fear of violence. This article discusses the unexpected findings from two recent adoption studies of previously looked after children in England and Wales. The studies exposed the prevalence of APV in the lives of families who had experienced an adoption disruption and those who were finding parenting very challenging. Two main APV patterns emerged: early onset (pre-puberty) that escalated during adolescence, and late onset that surfaced during puberty and rapidly escalated. The stigma and shame associated with APV delayed help seeking. The response from services was often to blame the adoptive parents and to instigate child protection procedures. There is an urgent need for a greater professional recognition of APV and for interventions to be evaluated with children who have been maltreated and showing symptoms of trauma.